2019
DOI: 10.3389/fpls.2019.01580
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Environmental Factors That Shape Genetic and Phenotypic Leaf Trait Variation in the Tree Qualea grandiflora Across the Brazilian Savanna

Abstract: Identifying the environmental factors that shape intraspecific genetic and phenotypic diversity of species can provide insights into the processes that generate and maintain divergence in highly diverse biomes such as the savannas of the Neotropics. Here, we sampled Qualea grandiflora, the most widely distributed tree species in the Cerrado, a large Neotropical savanna. We analyzed genetic variation with microsatellite markers in 23 populations (418 individuals) and phenotypic variation of 10 metamer traits (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 75 publications
2
16
1
Order By: Relevance
“…However, we did not detect a decrease of genetic diversity from the historical centre for both species. Nevertheless, phylogeographical and genetic studies in Q. grandiflora and A. crassiflora indicated that genetic diversity and structure were shaped by Quaternary climatic changes in both species (Buzatti et al, 2018(Buzatti et al, , 2019Ribeiro, Souza, et al, (2016). This apparent contradiction between results obtained here and phylogeographical studies indicating effects of past events on genetic diversity, and structure of these species, can be explained by several factors.…”
Section: Genetic Data and Cphcontrasting
confidence: 96%
See 4 more Smart Citations
“…However, we did not detect a decrease of genetic diversity from the historical centre for both species. Nevertheless, phylogeographical and genetic studies in Q. grandiflora and A. crassiflora indicated that genetic diversity and structure were shaped by Quaternary climatic changes in both species (Buzatti et al, 2018(Buzatti et al, , 2019Ribeiro, Souza, et al, (2016). This apparent contradiction between results obtained here and phylogeographical studies indicating effects of past events on genetic diversity, and structure of these species, can be explained by several factors.…”
Section: Genetic Data and Cphcontrasting
confidence: 96%
“…org/10.5061/dryad.n7dv6. For complete information about DNA extraction and amplification, and genotyping methods, please refer Buzatti et al, (2019) and Ribeiro, Souza, et al, (2016).…”
Section: Genetic and Functional Leaf Traits Datamentioning
confidence: 99%
See 3 more Smart Citations